A High-Fat Compared with a High-Carbohydrate Breakfast Enhances 24-Hour Fat Oxidation in Older Adults. Issue 2 (27th February 2018) - Bush, Nikki C; Resuehr, Holly ES; Goree, Laura Lee; Locher, Julie L; Bray, Molly S; Soleymani, Taraneh; Gower, Barbara A
Abstract: Background: The ability to oxidize fat is associated with a lower risk of chronic metabolic disease. Preclinical data in mice showed that a high-fat "breakfast" increased 24-h fat oxidation relative to a high-carbohydrate breakfast. Objectives: The objectives of this study were to determine whether the timing of macronutrient intake in humans affects daily fuel utilization and to examine associations between fuel utilization and metabolic indexes. Methods: Participants were 29 healthy sedentary men and women (aged 55–75 y) with a body mass index (kg/m 2 ) between 25 and 35. Participants were randomly assigned to receive either a high-fat breakfast (FB; 35% carbohydrate, 20% protein, 45% fat; n = 13) or a high-carbohydrate breakfast (CB; 60% carbohydrate, 20% protein, 20% fat; n = 16) for 4 wk while consuming a "neutral" lunch and dinner. Twenty-four-hour and postprandial respiratory quotients (RQs) were measured by whole-room indirect calorimetry. Insulin and glucose measures including insulin sensitivity were determined by an oral-glucose-tolerance test. Measures were taken at baseline and after the 4-wk intervention. Group-by-time interactions were determined by 2-factor repeated-measures mixed-model ANOVA. Pearson's correlation analyses were used to determine associations of 24-h RQs with metabolic measures after the intervention. Results: There was a significant group-by-time interaction for change in the 24-h RQ [FB (mean ± SD): 0.88 ± 0.02 to 0.86 ± 0.02; CB: 0.88 ± 0.02 for both; P < 0.05], breakfast RQ (FB: 0.88 ± 0.03 to 0.86 ± 0.03; CB: 0.89 ± 0.02 to 0.90 ± 0.02; P < 0.01), and lunch RQ (FB: 0.089 ± 0.03 to 0.85 ± 0.03; CB: 0.89 ± 0.03 for both; P < 0.01). In the CB group at follow-up, 24-h RQ was positively associated with fasting glucose ( r = 0.66, P < 0.05), glucose area under the curve (AUC) ( r = 0.51, P < 0.05), and insulin AUC ( r = 0.52, P < 0.05) and inversely associated with insulin sensitivity ( r = –0.51, P < 0.05). Conclusions: The macronutrient composition of breakfast affects substrate utilization throughout the day in older adults. The consumption of a high-fat, lower-carbohydrate breakfast may reduce the risk of metabolic disease. This trial was registered at www.clinicaltrials.gov as NCT03164200.